2014
DOI: 10.1104/pp.114.252437
|View full text |Cite
|
Sign up to set email alerts
|

Two Cytoplasmic Effectors of Phytophthora sojae Regulate Plant Cell Death via Interactions with Plant Catalases

Abstract: Plant pathogenic oomycetes, such as Phytophthora sojae, secrete an arsenal of host cytoplasmic effectors to promote infection. We have shown previously that P. sojae PsCRN63 (for crinkling- and necrosis-inducing proteins) induces programmed cell death (PCD) while PsCRN115 blocks PCD in planta; however, they are jointly required for full pathogenesis. Here, we find that PsCRN63 alone or PsCRN63 and PsCRN115 together might suppress the immune responses of Nicotiana benthamiana and demonstrate that these two cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 45 publications
4
132
0
Order By: Relevance
“…Interestingly, some pathogen effectors have been shown to promote virulence by interfering with ROS induction. For example, the Ustilago maydis fungal effector Pep1, contributes to the penetration of the host epidermis by inhibiting apoplastic plant peroxidases (Hemetsberger et al, 2012), while the Phytophthora sojae effector CRN 115 decrease H 2 O 2 accumulation during infection through interaction with plant catalases (Zhang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some pathogen effectors have been shown to promote virulence by interfering with ROS induction. For example, the Ustilago maydis fungal effector Pep1, contributes to the penetration of the host epidermis by inhibiting apoplastic plant peroxidases (Hemetsberger et al, 2012), while the Phytophthora sojae effector CRN 115 decrease H 2 O 2 accumulation during infection through interaction with plant catalases (Zhang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Wawra et al (80) reported C-terminally mediated PI3P binding of AVR3a from P. infestans, while Sun et al (81) found similar binding properties within the Avh5 effector of P. sojae, although the latter concluded that both regions were involved in effector entry into cells. Notably, Zhang et al (54) showed that phospholipid binding of the RXLR effector AVR3a can occur even with denatured proteins, but mutants in the C terminus of AVR3a (79), known to impair phospholipid binding, were not assessed in that study. Our idea of a conserved hosttargeting domain within effectors continues to be challenged by these conflicting findings on the functional relevance of such a domain.…”
Section: How Are Effectors Deployed In the Host?mentioning
confidence: 99%
“…These effectors act through direct interaction with catalases to overcome host immune responses (54).…”
Section: Effectors Suppress Host Immunitymentioning
confidence: 99%
“…Pepper leaves were infected with P. capsici zoospores suspension (Zhang et al . ). Detached pepper leaves were inoculated with 10 μ L of zoospore suspension (100 zoospores per μ L) and incubated in the dark at 25°C.…”
Section: Methodsmentioning
confidence: 97%